Determination of individual coumarin in a dry extract of Melilotus officinalis L. - M. V. Aroyan; Yu. E. Generalova; I. I. Terninko; I. E. Kaukhova; E. K. Novikova (Разработка и регистрация лекарственных средств, 2021)
Introduction. Substances of plant origin exhibit a variety of pharmacological activity in combination with a relatively low toxicity and frequency of side effects. In this regard, a promising direction is the standardization of substances of plant origin in the development of new herbal medicinal products.Aim. Qualitative and quantitative determination of individual coumarin in a dry extract of Melilotus оfficinalis L.Materials and methods. A dry extract of the Melilotus officinalis L. was used as an object of research. Determination of individual coumarin was carried out by high-performance liquid chromatography.Results and discussion. As a result of the research, coumarin was identified by high performance liquid chromatography based on comparison of retention times of the sample with retention times of a standard sample of coumarin in the sample of dry extract under research. The coumarin contents in the dry extract was 0.642 ± 0.007 %.Conclusion. The data obtained on the qualitative and quantitative content of coumarin in the dry extract of Melilotus оfficinalis L. were used in the development of the draft version specification of quality indicators.